2020
DOI: 10.1101/2020.08.18.255315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In-depth blood proteome profiling analysis revealed distinct functional characteristics of plasma proteins between severe and non-severe COVID-19 patients

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has infected over ten million patients worldwide. Although most coronavirus disease 2019 (COVID-19) patients have a good prognosis, some develop severe illness. Markers that define disease severity or predict clinical outcome need to be urgently developed as the mortality rate in critical cases is approximately 61.5%. In the present study, we performed in-depth proteome profiling of undepleted plasma from eight COVID-19 patients. Quantitative pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…Similarly, proteomic and metabolomics profiling of serum samples obtained from 46 COVID-19 and 53 control individuals showed deregulation of three major pathways namely complement system, macrophage function and platelet degranulation in severe COVID-19 patients [47]. Study by Park J et al, employed an in-depth proteome profiling of undepleted plasma revealed signatures of proteins involved in neutrophil activation, platelet function, and T cell suppression [3]. Based on the findings, this study's investigators have proposed specific plasma proteins as predictive biomarkers of COVID-19 [3].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, proteomic and metabolomics profiling of serum samples obtained from 46 COVID-19 and 53 control individuals showed deregulation of three major pathways namely complement system, macrophage function and platelet degranulation in severe COVID-19 patients [47]. Study by Park J et al, employed an in-depth proteome profiling of undepleted plasma revealed signatures of proteins involved in neutrophil activation, platelet function, and T cell suppression [3]. Based on the findings, this study's investigators have proposed specific plasma proteins as predictive biomarkers of COVID-19 [3].…”
Section: Resultsmentioning
confidence: 99%
“…Study by Park J et al, employed an in-depth proteome profiling of undepleted plasma revealed signatures of proteins involved in neutrophil activation, platelet function, and T cell suppression [3]. Based on the findings, this study's investigators have proposed specific plasma proteins as predictive biomarkers of COVID-19 [3]. In a different study, proteomic analysis of serum samples from early COVID-19 patients also identified differentially expressed proteins known to have a function in SARS-CoV-2 infection-associated inflammation and immune signaling [4].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, some studies suggest that SARS-CoV-2 can be found in the blood, and can induce the disease and cause both cellular and systemic dysfunction 36,42,46 . While this question is beyond the scope of this work, it is important to note that if future studies do identify the active form of SARS-CoV-2 in human blood, then the implications of our findings will apply to this systemic response as well 47,48 .…”
Section: Discussionmentioning
confidence: 96%
“…Both have been confirmed to be expressed in upper airway tissues ( Fink et al, 2013 ; Clifford et al, 2016 ). As for their respective capacities for distinguishing upper airway samples from different subjects under various pathological conditions, LAGLS3BP has a specific expression level following the activation of neutrophil-mediated immune responses, which is generally observed during viral infections ( Andres-Terre et al, 2015 ; Xu et al, 2019 ) including but not restricted to SARS-CoV-2 infection ( Didangelos, 2020 ; Park et al, 2020 ). Therefore, LAGLS3BP may also help in distinguishing samples from disease controls and those from patients with viral infection but not the detailed subgrouping of infections.…”
Section: Discussionmentioning
confidence: 99%